2002
DOI: 10.1111/1540-6237.00097
|View full text |Cite
|
Sign up to set email alerts
|

Existing Diversity and Judicial Selection: The Role of the Appointment Method in Establishing Gender Diversity in State Supreme Courts

Abstract: Objectives. To explore differences in the appointment and election method of selecting state high court justices in promoting gender diversity, and to explore the effect of existing gender diversity within the political institutions on the selection of women to office. Methods. Our data include all justices who have been selected to state courts of last resort from 1980 through 1997. We use logistic regression analysis to test the effect of existing gender diversity on a high court on the likelihood that a wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 28 publications
1
73
2
Order By: Relevance
“…Our preliminary finding fits with what scholars of judicial politics in the United States have found: the chances that a woman will become a high court judge do not seem to depend on whether judges are elected or whether judges are appointed (Alozie 1990;Bratton and Spill 2002;Frederick and Streb 2008;Click and Emmert 1987;Hurwitz and Lanier 2003;Martin and Pyle 2002;Williams 2007). Comparative studies of women's presence on high courts are more mixed, with some finding that judicial elections may favor women and minorities (Driscoll and Nelson 2015) and others finding that high courts are likelier to have more women if appointment is centralized in the presidency (Valdini and Shortell 2014;Williams and Thames 2008).…”
Section: Explanation 2: Selection Methodssupporting
confidence: 88%
“…Our preliminary finding fits with what scholars of judicial politics in the United States have found: the chances that a woman will become a high court judge do not seem to depend on whether judges are elected or whether judges are appointed (Alozie 1990;Bratton and Spill 2002;Frederick and Streb 2008;Click and Emmert 1987;Hurwitz and Lanier 2003;Martin and Pyle 2002;Williams 2007). Comparative studies of women's presence on high courts are more mixed, with some finding that judicial elections may favor women and minorities (Driscoll and Nelson 2015) and others finding that high courts are likelier to have more women if appointment is centralized in the presidency (Valdini and Shortell 2014;Williams and Thames 2008).…”
Section: Explanation 2: Selection Methodssupporting
confidence: 88%
“…Leading studies in the field rely on cross-sectional designs and linear or logistic regression (e.g., Williams and Thames, 2008;Bratton and Spill, 2002). Although these designs are potentially valid, as Hoekstra (2010) and Hoekstra, Kittilson and Bond (2014) note, they rely on a number of assumptions that may not hold in practice.…”
Section: Strengthen Research Designmentioning
confidence: 99%
“…Studies have suggested that executive appointment mechanisms promote greater diversity on courts by ensuring clear accountability; clear accountability facilitates the imposition of sanctions for homogenous selections and also allows for credit claiming for diverse selections (Bratton and Spill, 2002;Williams and Thames, 2008;Valdini and Shortell, 2016). This argument suggests that appointment mechanisms in which multiple actors play a role are subject to coordination failures as one actor can blame another for a failure to diversify.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Service in high-status offices is thought to conflict with sex-role socialization and family responsibilities. Merit selection systems in particular are designed to reduce the emphasis on patronage and public opinion (Bratton & Spill, 2002). …”
Section: Literature Reviewmentioning
confidence: 99%